Halogen Bonding Helicates Encompassing Iodonium Cations. Issue 27 (6th June 2019) - Vanderkooy, Alan; Gupta, Arvind Kumar; Földes, Tamás; Lindblad, Sofia; Orthaber, Andreas; Pápai, Imre; Erdélyi, Máté
Abstract: The first halonium‐ion‐based helices were designed and synthesized using oligo‐aryl/pyridylene‐ethynylene backbones that fold around reactive iodonium ions. Halogen bonding interactions stabilize the iodonium ions within the helices. Remarkably, the distance between two iodonium ions within a helix is shorter than the sum of their van der Waals radii. The helical conformations were characterized by X‐ray crystallography in the solid state, by NMR spectroscopy in solution and corroborated by DFT calculations. The helical complexes possess potential synthetic utility, as demonstrated by their ability to induce iodocyclization of 4‐penten‐1‐ol. Abstract : Reactive halogen bonding helices : Iodonium cations are stabilized via three‐center, four‐electron [N−I−N] + halogen bonds with oligomeric pyridyl ligands. Complexation of the iodonium ions produces new helical structures as predicted by DFT calculation and confirmed by X‐ray crystallography and NOE spectroscopy. The helices were also shown to be reactive in a halofunctionalization reaction.